Clad steel plate, its manufacturing method and welded structure
The clad steel sheet design with controlled interface nanohardness and composition addresses hydrogen embrittlement issues, ensuring structural integrity and cost-effectiveness in welding applications.
Patent Information
- Application Number
- JP2020142382
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-08-26
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2040-08-26
AI Technical Summary
Clad steel sheets made of stainless steel or Ni-based alloys face issues with hydrogen embrittlement due to elemental diffusion and martensitic transformation at the interface, leading to potential peeling and structural failure during welding, especially when using hydrogen as a welding gas.
A clad steel sheet design with a base material of carbon steel or low alloy steel, a combined material of corrosion-resistant alloy, and an insert material between them, controlled to have a nanohardness of 7GPa or more within a 5 μm width at the interface, using specific composition and manufacturing conditions to suppress martensitic transformation and hydrogen embrittlement.
The solution provides clad steel sheets with excellent hydrogen embrittlement resistance, preventing peeling and ensuring structural integrity during welding, even with hydrogen gas use, while reducing material and welding costs.
Smart Images

Figure 0007628404000005 
Figure 0007628404000001 
Figure 0007628404000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a clad steel plate having excellent hydrogen embrittlement resistance at the joining surface, a manufacturing method thereof, and a welded structure manufactured using the clad steel plate in a manufacturing process including welding or gouging using a gas containing hydrogen. [Background technology]
[0002] Stainless steels and Ni-based alloys have excellent corrosion resistance and are therefore suitable for use in severe corrosive environments. Examples of the corrosive environments mentioned above include oil well environments, high chloride environments exposed to seawater or brackish water, and plant equipment and chemical tankers exposed to various acid solutions. In these corrosive environments, stainless steels and Ni-based alloys are used in seawater desalination plants, flue gas desulfurization equipment, chemical storage tanks, structural components such as oil well tubular goods, pumps and valves, heat exchangers, etc.
[0003] On the other hand, stainless steels and Ni-based alloys (hereinafter collectively referred to as "high alloy steels") contain large amounts of alloying elements such as Cr, Ni, and Mo to ensure corrosion resistance, and compared to carbon steels and low alloy steels, the cost of materials, as well as the costs of processing and welding, are high. Prices can also fluctuate significantly due to rising prices of alloying elements. For this reason, their use may be restricted mainly due to cost.
[0004] As mentioned above, when considering the cost aspect, it is effective to use clad steel plate as a material from the viewpoint of processing and welding. Clad steel plate is a material in which two or more different metals are bonded together. Compared to steel plate consisting only of high alloy steel (hereinafter referred to as "solid steel plate"), clad steel plate can reduce the amount of high alloy steel used, reducing material costs, and also reduces the number of dissimilar material welding points, thereby reducing the cost of welding materials.
[0005] In addition, in clad steel plates, by bonding a material with excellent properties to a base material (hereinafter, the bonded material will be referred to as the "clad material"), it is possible to obtain the excellent properties of both the clad material and the base material.
[0006] For example, a high alloy steel having the characteristics required for the use environment may be used for the cladding material, and a carbon steel or low alloy steel having the toughness and strength required for the use environment may be used for the base material. In such a case, not only can the cost be reduced as described above, but the characteristics equivalent to those of a solid steel plate and the strength and toughness equivalent to those of carbon steel and low alloy steel can be ensured. This allows both economical and functional compatibility.
[0007] In light of the above, the need for clad steel plates using stainless steel or Ni-based alloys has been increasing in recent years in various industrial fields. However, when using clad steel plates, it is important to prevent peeling at the joint between the clad material and the base material. If the clad material and the base material peel off during use, the desired properties such as corrosion resistance and strength may not be obtained. In addition, there may be a risk of holes being formed in the structure or the structure collapsing. Therefore, it is important to prevent peeling between the clad material and the base material in clad steel.
[0008] Patent Document 1 discloses a technology for producing austenitic stainless steel clad plate in which the reduction ratio, calculated as plate thickness before rolling / plate thickness after rolling, is set to 1.5 or more at 950°C or higher, and hot rolling is performed in controlled rolling in a temperature range of 900°C or lower with a cumulative reduction rate of 50% or more and a rolling end temperature of 750°C or higher, followed by accelerated cooling with a cooling rate of 3°C / s or more and a cooling stop temperature of 550°C or higher, and then allowed to cool, thereby producing a clad steel plate with excellent low-temperature toughness and HAZ toughness of the base material and corrosion resistance of the clad material.
[0009] There are many techniques for improving joint strength by specifying the reduction ratio at high temperatures, including Patent Document 1. The joint strength in these documents refers to the strength of the manufactured steel plate, and is evaluated, for example, by a shear strength test according to JIS G 0601.
[0010] However, clad steel plates are actually used in structures assembled by various welding processes, so the effect of welding on delamination must also be considered.
[0011] Patent Document 2 discloses a technique for preventing delayed fracture of martensite at the interface by specifying the temperature and time of tempering after rolling for an austenitic stainless clad steel sheet. In addition, Non-Patent Document 1 evaluates the hydrogen embrittlement susceptibility of martensite at the interface of clads of SUS316L and Inconel 625. Patent Document 3 specifically discloses, by way of examples, a technique in which a 100 μm-thick Ni insert material is inserted into a duplex stainless clad steel plate, and the plate is heated to 1240° C. or 1200° C. and rolled. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Patent No. 6127939 [Patent Document 2] Japanese Patent Application Publication No. 6-7803 [Patent Document 3] Japanese Patent Application Publication No. 62-110880 [Non-patent literature]
[0013] [Non-Patent Document 1] Kushida et al., Iron and Steel, Vol. 75 (1989), p. 1508 Summary of the Invention [Problem to be solved by the invention]
[0014] In clad steel plates made of stainless steel or Ni-based alloys, Cr and Ni diffuse from the clad material to the base material, and C diffuses from the base material to the clad material during heating during rolling, creating a diffusion layer of elements at the interface. The concentration of each element in the diffusion layer gradually changes, but depending on the element concentration, martensite may form during cooling after rolling in a region where the temperature at which martensitic transformation begins is high and the critical cooling rate at which martensitic transformation occurs is slow.
[0015] In normal use or welding, the martensite at the interface does not affect interfacial peeling. However, for example, when welding a clad steel plate with thick interfacial martensite and high hardness using hydrogen as the welding gas, hydrogen will enter the martensite and stress will be generated at the interface due to structural stress, deformation during welding, and transformation of the base material near the weld, and it is thought that this combination may cause hydrogen embrittlement.
[0016] The inventors recognized that the higher the hardness of martensite, the higher the susceptibility to hydrogen embrittlement, and further, that the greater the width of martensite in the diffusion layer, the greater the risk that minute hydrogen embrittlement will lead to large interfacial peeling. Furthermore, the inventors discovered that the problem to be solved in order to suppress interfacial peeling of cladding due to hydrogen embrittlement during welding is to control the hardness and width of martensite at the interface, the hydrogen concentration in the steel, and the stress applied to martensite.
[0017] The above-mentioned Patent Document 2 discloses a technology for preventing delayed fracture of martensite at the interface. However, this technology is for preventing delayed fracture during manufacturing, and no technology for preventing delayed fracture in welded structures is disclosed. In addition, since an additional tempering process leads to increased costs, a technology for improving the hydrogen embrittlement resistance of martensite at the interface without tempering is practically required, but no solution to this problem is disclosed or suggested. The above-mentioned Non-Patent Document 1 describes a method for evaluating the hydrogen embrittlement susceptibility of martensite at the interface. However, in actual clad steel, the width of the diffusion layer is presumed to vary depending on the heating temperature and rolling reduction ratio, but there is no description or suggestion of the relationship between the width of the diffusion layer and hydrogen embrittlement susceptibility.
[0018] When manufacturing clad steel plates, an insert material is sometimes inserted between the clad material and the base material in order to suppress element diffusion at the interface and the associated precipitation of Cr carbonitrides and intermetallic compounds (see Patent Document 3). As this insert material, a foil or plating of pure Ni or an alloy containing a large amount of Ni, which has an FCC structure at high temperatures and a relatively small diffusion coefficient of elements, is sometimes used.
[0019] As a result of intensive research, the inventors found that inserting such an insert material suppresses the martensitic transformation because Ni is an austenite stabilizing element, and tends to suppress interfacial peeling of the clad due to hydrogen embrittlement during welding. Furthermore, the inventors assumed that depending on the thickness of the insert material, the heating temperature, and the time, elements may diffuse beyond the insert material, causing martensite to form at the interface between the cladding material and the insert material or the interface between the base material and the insert material, resulting in hydrogen embrittlement, and found that this is a problem to be solved when using an insert material.
[0020] Although Patent Document 3 discloses a technique for inserting a 100 μm Ni insert material into a duplex stainless clad steel plate, it does not disclose the heating time or the martensite phase at the interface.
[0021] In view of the above-mentioned problems, the present invention aims to provide a clad steel plate having excellent hydrogen embrittlement resistance and good hydrogen embrittlement resistance at the joining surface, a manufacturing method thereof, and a welded structure. [Means for solving the problem]
[0022] The present invention has been made to solve the above-mentioned problems, and the gist of the present invention is the following clad steel plate, its manufacturing method, and welded structure. [1] A clad steel plate having a base material and a clad material joined to the base material, The base material is made of carbon steel or low alloy steel, The cladding material is made of a corrosion-resistant alloy, The structure is such that an insert material is inserted between the base material and the cladding material. A clad steel plate characterized in that at the interface between the base material and the insert material of the clad steel plate, the width in the plate thickness direction of a region having a nano-hardness of 7 GPa or more is 5 μm or less. [2] The clad steel plate according to claim 1, wherein the composition of the base material contains, in mass%, C: 0.020-0.200%, Si: 1.00% or less, Mn: 0.10-3.00%, P: 0.050% or less, S: 0.050% or less, Ceq is 0.20-0.40, and the balance is Fe and impurities, where Ceq is defined by the following formula (1): Ceq=C+Mn / 6+(Cu+Ni) / 15+(Cr+Mo+V) / 5...Equation (1) In the formula, C, Mn, Cu, Ni, Cr, Mo and V are the contents (mass%) of each element in the chemical composition of the base steel plate. [3] The clad steel plate according to [2], wherein the composition of the base metal further contains, in mass%, one or more selected from Ni: 0.01-1.00%, Cr: 0.01-1.00%, Mo: 0.01-0.50%, Cu: 0.01-1.00%, Co: 0.01-0.50%, Se+Te: 0.01-0.10%, V: 0.001-0.100%, Ti: 0.001-0.200%, Nb: 0.001-0.200%, Al: 0.005-0.300%, Ca: 0.0003-0.0050%, B: 0.0003-0.0030% and REM: 0.0003-0.0100%, in place of a portion of the Fe. [4] The clad steel plate according to any one of [1] to [3], characterized in that a clad material of the clad steel plate is a stainless steel or a nickel-based alloy containing, by mass%, 10% or more of Cr. [5] The clad steel plate according to any one of [1] to [4], wherein the insert material contains, by mass%, Ni: 20% or more and Cr: less than 10%. [6] A method for manufacturing a clad steel plate according to any one of [1] to [5], comprising inserting an insert material between a base material and a clad material, laminating the materials so that the bonding surface is vacuumed, and sealing the four periphery of the bonding surface by welding to form a clad material, and assembling one or more of the clad materials into a clad rolled material, heating the clad material such that the value d (μm) of the clad heating parameter calculated from Equation (2) using the maximum heating temperature Temp (°C) in the heating furnace and the time Time (min) from the time when the heating temperature in the heating furnace reaches the maximum heating temperature Temp-20°C to the time of removal from the heating furnace is less than the value of the thickness Thick (μm) of the inserted insert material, followed by hot rolling, and setting the width in the plate thickness direction of the region where the nano-hardness of the interface between the base material and the clad material is 7 GPa or more to 5 μm or less. d=2.27×10 5 ×√(Time)×exp(-1.64×10 4 / (Temp+273))...Equation (2) [7] A welded structure made using the clad steel plate according to any one of [1] to [5]. [8] The clad steel plate according to any one of [1] to [5], characterized in that the clad steel plate is used for welding using hydrogen as a welding gas. Effect of the Invention
[0023] According to the present invention, it is possible to obtain a clad steel plate having good hydrogen embrittlement resistance at the bonding surface. [Brief description of the drawings]
[0024] [Figure 1] FIG. 4 is a diagram showing the effect of the relationship of formula (2) on hydrogen embrittlement resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] The present inventors conducted the following study to address the above-mentioned problem. Specifically, in clad steel plates made of various stainless steels and Ni-based alloys, the composition and thickness of the insert material, the heating temperature and heating time of the material were changed to investigate element diffusion and metal structure at the interface, and the relationship with hydrogen embrittlement resistance at the interface was evaluated. As a result, the following findings (a) and (b) were obtained. Hereinafter, nanohardness refers to the hardness of a material evaluated in accordance with the instrumented indentation hardness test (also called nanoindentation test) specified in ISO 14577.
[0026] (a) The thinner the region with a nano-hardness of 7 GPa or more near the interface between the base material and the insert material of the clad steel plate, the lower the susceptibility of the clad steel plate to hydrogen embrittlement. For this reason, it is effective to make the region with a nano-hardness of 7 GPa or more 5 μm or less.
[0027] (b) In the rolled material of clad steel plate, the base material carbon steel or low alloy steel is in contact with the cladding material stainless steel or Ni-based alloy sandwiching the insert material. The profile of alloy elements at the interface could be organized by the temperature and time of material heating and the rolling reduction ratio. It was also confirmed that when a cladding material containing 10% or more Cr by mass was used and Cr diffused beyond the thickness of the insert material, a region with a nanohardness of 7 GPa or more was generated near the interface between the base material and the insert material of the clad steel plate. This is because Cr diffuses the fastest compared to Ni and is an element that increases hardenability, so martensitic transformation occurs in the region where the Cr content is high and the content of austenite stabilizing elements such as Ni is low.
[0028] Therefore, in order to obtain a clad steel plate having excellent hydrogen embrittlement resistance at the joining surface, it is necessary to control the Cr diffusion during heating according to the thickness of the insert material. The present invention was made based on the above findings. Each requirement of the present invention will be described in detail below.
[0029] 1. Configuration of the present invention The clad plate according to the present invention comprises a base material, an insert material bonded to the base material, and a clad material bonded to the insert material. The base material is made of carbon steel or low alloy steel as described below. The clad material is made of a corrosion-resistant alloy, and examples of the corrosion-resistant alloy include stainless steel containing 10% or more of Cr and Ni-based alloys. Examples of the insert material include an alloy containing 20% or more of Ni and less than 10% of Cr, and pure Ni. Furthermore, the width in the plate thickness direction of a region having a nano-hardness of 7 GPa or more at the interface between the base material and the insert material is 5 μm or less.
[0030] 2. Characteristics of the cladding interface The interface characteristics of the clad steel plate according to the present invention will now be described. In order to obtain a clad steel plate having good hydrogen embrittlement resistance at the bonding surface, it is necessary to suppress the formation of a hard martensite phase at the clad interface.
[0031] 2-1. Nano-hardness of the interface between the base material and the insert material of clad steel plate At the interface between the base material and the insert material of the clad steel plate, the width in the plate thickness direction of the region with a nano-hardness of 7 GPa or more is 5 μm or less. If the width in the plate thickness direction of the region with a nano-hardness of 7 GPa or more exceeds 5 μm, the region of hard martensite that is highly susceptible to hydrogen embrittlement is large, and the interface may peel off when welding is performed using a welding gas containing hydrogen. It is preferably 3 μm or less, and more preferably 1 μm or less. The smaller the region with a nano-hardness of 7 GPa or more, the lower the susceptibility to hydrogen embrittlement, so no lower limit is set.
[0032] 3. Composition of the base material The base material is made of carbon steel or low alloy steel. The base material preferably has a composition, in mass%, of C: 0.020-0.200%, Si: 1.00% or less, Mn: 0.10-3.00%, P: 0.050% or less, S: 0.050%, Ceq is 0.20-0.40, and the balance is Fe and impurities. Here, Ceq is defined by the following formula (1). Ceq=C+Mn / 6+(Cu+Ni) / 15+(Cr+Mo+V) / 5...Equation (1) In the formula, C, Mn, Cu, Ni, Cr, Mo, and V are the contents (mass%) of each element in the composition of the base material.
[0033] C is an element that improves the strength of steel, and sufficient strength is achieved by including it in an amount of 0.020% or more. However, if it exceeds 0.200%, it will cause deterioration in weldability and toughness. Therefore, the C content is set to 0.020 to 0.200%, preferably 0.040% or more, and more preferably 0.050% or more. On the other hand, the upper limit is preferably 0.100% or less, and more preferably 0.080% or less. A more preferable range is 0.040% to 0.100%, and an even more preferable range is 0.050% to 0.080%.
[0034] Silicon is effective for deoxidization and is an element that improves the strength of steel. However, if the content exceeds 1.00%, it will cause deterioration of the surface properties and toughness of the steel. Therefore, the amount of silicon is set to 1.00% or less, and preferably 0.50% or less. Silicon may not be contained. The preferable lower limit of the silicon content is 0.01%.
[0035] Mn is an element that increases the strength of steel, and this effect is manifested by including it in an amount of 0.10% or more. However, if it exceeds 3.00%, the weldability is impaired and the alloy cost increases. Therefore, the Mn content is set to 0.10 to 3.00%, preferably 0.50 to 2.00%, and more preferably 0.90% to 1.60%.
[0036] P is an impurity in steel, and if the content exceeds 0.050%, toughness deteriorates. Therefore, the P content is set to 0.050% or less, and preferably 0.020% or less.
[0037] S is an impurity in steel, and if the content exceeds 0.050%, toughness deteriorates. Therefore, the S content is set to 0.050% or less, and preferably 0.010% or less.
[0038] Ceq (carbon equivalent) is a value used to estimate hardness and weldability from the component composition of steel, and is calculated by formula (1). The higher Ceq, the higher the hardness and the worse the weldability. If Ceq is less than 0.20, sufficient strength for a structure cannot be obtained. Therefore, Ceq is set to 0.20 or more, and preferably 0.23 or more. If Ceq exceeds 0.40, weldability deteriorates, and interpass temperature control and post heat treatment become necessary, increasing welding costs. Therefore, Ceq is set to 0.40 or less, and preferably 0.35 or less. Ceq=C+Mn / 6+(Cu+Ni) / 15+(Cr+Mo+V) / 5...Equation (1) In the formula, C, Mn, Cu, Ni, Cr, Mo, and V are the contents (mass%) of each element in the composition of the base material.
[0039] The composition of the base material may further contain, in mass %, one or more selected from Ni: 0.01-1.00%, Cr: 0.01-1.00%, Mo: 0.01-0.50%, Cu: 0.01-1.00%, Co: 0.01-0.50%, Se+Te: 0.01-0.10%, V: 0.001-0.100%, Ti: 0.001-0.200%, Nb: 0.001-0.200%, Al: 0.005-0.300%, Ca: 0.0003-0.0050%, B: 0.0003-0.0030% and REM: 0.0003-0.0100%, in place of a portion of the Fe.
[0040] Ni is an element that improves the hardenability of steel, and improves the strength and toughness of steel after rolling. However, if it exceeds 1.00%, it causes deterioration of weldability and toughness. Therefore, when Ni is contained, the Ni amount is 1.00% or less. It is preferably 0.50% or less, and more preferably 0.30% or less. The preferable lower limit of the Ni content is 0.01%.
[0041] Cr is an element that improves the hardenability of steel, and improves the strength and toughness of the steel after rolling. However, if it exceeds 1.00%, it causes deterioration of weldability and toughness. Therefore, when Cr is contained, the Cr amount is set to 1.00% or less, preferably 0.50% or less, and more preferably 0.30% or less. The preferred lower limit of the Cr content is 0.01%.
[0042] Mo is an element that improves the hardenability of steel, and improves the strength and toughness of steel after rolling. However, if it exceeds 0.50%, it causes deterioration of weldability and toughness. Therefore, when Mo is contained, the Mo content is set to 0.50% or less. It is preferably 0.30% or less, and more preferably 0.1% or less. The preferred lower limit of the Mo content is 0.01%.
[0043] Cu is an element that improves the hardenability of steel, and improves the strength and toughness of steel after rolling. However, if it exceeds 1.00%, it causes deterioration of weldability and toughness. Therefore, when Cu is contained, the Cu content is set to 1.00% or less. It is preferably 0.50% or less, and more preferably 0.30% or less. The preferred lower limit of the Cu content is 0.01%.
[0044] Co is an element that improves the hardenability of steel, and improves the strength and toughness of the steel after rolling. However, if it exceeds 0.50%, hot workability is impaired and productivity decreases. Therefore, when Co is contained, the Co amount is set to 0.50% or less. It is preferably 0.30% or less, and more preferably 0.1% or less. The preferred lower limit of the Co content is 0.01%.
[0045] Se and Te suppress easily oxidizable elements such as Mn, Si, and Al in the steel sheet from diffusing to the steel sheet surface to form oxides, improving the surface properties and galvanic properties of the steel sheet. However, this effect saturates when the total amount exceeds 0.10%. Therefore, when Se and Te are added, the total amount of Se and Te is set to 0.10% or less, and more preferably 0.05% or less. The preferred lower limit of the Se+Te content is 0.01%.
[0046] Al is an element that is effective in deoxidizing steel. However, if it exceeds 0.300%, it causes deterioration of the toughness of the welded part. Therefore, if Al is contained, the Al content is set to 0.300% or less, and preferably 0.100% or less. The preferable lower limit of the Al content is 0.005%.
[0047] V increases the strength of steel by forming carbonitrides. However, if it exceeds 0.100%, it causes deterioration of weldability and toughness. Therefore, if V is contained, the V content is set to 0.100% or less, preferably 0.050% or less. The preferred lower limit of the V content is 0.001%.
[0048] Ti is an element that refines crystal grains and increases strength, and this effect is manifested when added at 0.001% or more. However, if it exceeds 0.200%, weldability is impaired and the alloy cost increases. Therefore, the Ti content is set to 0.001 to 0.200%, preferably 0.005 to 0.100%, and more preferably 0.010 to 0.050%.
[0049] Nb is an element that raises the recrystallization temperature, and its effect is manifested by adding 0.001% or more. However, if it exceeds 0.200%, the weldability is impaired and the alloy cost increases. Therefore, the Nb content is set to 0.001 to 0.200%, preferably 0.005 to 0.100%, and more preferably 0.010 to 0.050%.
[0050] Ca refines the structure of the weld heat affected zone and improves toughness. However, if it exceeds 0.0050%, it forms coarse inclusions and deteriorates toughness. Therefore, when Ca is contained, the Ca content is set to 0.0050% or less, preferably 0.0030% or less. The preferred lower limit of the Ca content is 0.0003%.
[0051] B is an element that improves the hardenability of steel, and improves the strength and toughness of the steel after rolling. However, if it exceeds 0.0030%, it causes deterioration of weldability and toughness. Therefore, when B is contained, the B content is set to 0.0030% or less, and preferably 0.0020% or less. The preferred lower limit of the B content is 0.0003%.
[0052] REM refines the structure of the weld heat affected zone and improves toughness. However, if it exceeds 0.0100%, it forms coarse inclusions and deteriorates toughness. Therefore, if REM is contained, the REM content is set to 0.0100% or less, preferably 0.005% or less. The preferred lower limit of the REM content is 0.0003%.
[0053] Here, REM is a collective term for 17 elements, including 15 lanthanoid elements plus Y and Sc. One or more of these 17 elements can be contained in a steel material, and the REM content means the total content of these elements.
[0054] In the composition of the base metal of the present invention, the balance is Fe and impurities. Here, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of steel materials, and are permissible within a range that does not adversely affect the present invention.
[0055] 4. Cladding material The cladding material of the present invention is made of a corrosion-resistant alloy. It is preferable that the corrosion-resistant alloy is a stainless steel or nickel-based alloy containing 10% or more of Cr. As described above, the corrosion-resistant alloy contains a large amount of Cr, and the diffusion of Cr increases the hardenability of the cladding interface and makes it easier to transform into martensite, while carbon on the base material side diffuses to the cladding material side, forming a hard martensite phase at the base material side interface, which causes a decrease in hydrogen embrittlement resistance of the joint surface. That is, the effect of the present invention is exerted when a corrosion-resistant alloy containing a large amount of Cr is used. If the Cr content of the cladding material is 10% or more, the effect of applying the present invention is remarkable. If the Cr content is 15% or more, the effect can be exerted more remarkable.
[0056] 5. Insert material The insert material of the present invention is preferably an alloy containing Ni: 20% or more and Cr: less than 10% by mass. As described above, Ni is an element that stabilizes austenite and suppresses martensitic transformation, and Cr is an element that enhances hardenability and promotes martensitic transformation. The effect of the present invention is exerted when an insert material having a Ni content of 20% or more and a Cr content of less than 10% is used. The Ni content is preferably 30% or more, and more preferably 50% or more. The higher the Ni content, the more the martensitic transformation is suppressed, so no upper limit is set. In addition, since the diffusion rate of Cr in the Fe matrix is faster than the diffusion rate of Ni, when the Cr content of the insert material is high, a region where only Cr is high and the content of austenite stabilizing elements such as Ni is low occurs on the base material side regardless of the Ni content. For this reason, the Cr content of the insert material is less than 10%. The Cr content is preferably less than 5%, and more preferably less than 1%. The lower the Cr content, the more the martensitic transformation is suppressed, so no lower limit is set. There are no particular restrictions on the other elements, but the following elements are likely to form oxides, carbides, and nitrides: B, Al, Si, Ti, Nb, Mg, REM, and Ca. If these elements precipitate at the interface, they will cause poor bonding or fracture starting points, reducing peel resistance. Therefore, it is desirable for each content to be less than 1%.
[0057] The present invention relates to a technology for a clad steel plate having excellent hydrogen embrittlement resistance at the bonding surface by controlling the bonding interface structure, and a manufacturing method thereof, and the type and classification of the cladding material and the insert material are not particularly specified. Examples of cladding materials include stainless steel and nickel-based alloys. Stainless steels include austenitic stainless steel, ferritic stainless steel, and duplex stainless steel, while nickel-based alloys have various alloy compositions under the trade names of Inconel, Incoloy, and Hastelloy. Examples of insert materials include Ni alloys and pure Ni. Ni alloys have various alloy compositions under the trade names of Invar alloy and Permalloy.
[0058] 6. Manufacturing method The manufacturing method of the clad steel plate according to the present invention will be described. As described above, in order to obtain good hydrogen embrittlement resistance of the joint surface, it is necessary to control the metal structure, and such a metal structure can be realized by combining the composition of the steel and the insert material with appropriate manufacturing conditions. In the above-mentioned clad steel plate, an insert material is inserted between the base material and the clad material, the layers are stacked so that the bonding surface is vacuum, and the four periphery of the bonding surface is sealed by welding to form a clad material. The clad rolled material assembled from one or more of the above-mentioned clad materials is heated so that the value of the clad heating parameter d (μm), calculated from equation (2) using the maximum heating temperature Temp (℃) in the heating furnace and the time Time (minutes) from the time when the heating temperature in the heating furnace reaches the maximum heating temperature Temp-20℃ to the time of removal from the heating furnace, is less than the value of the thickness Thick (μm) of the inserted insert material, and then hot rolling is performed to produce the clad steel plate. d=2.27×10 5 ×√(Time)×exp(-1.64×10 4 / (Temp+273))...Equation (2)
[0059] 6-1.Clad materials The clad material is manufactured by the method described below. First, specifically, the carbon steel and low alloy steel as the base material and the corrosion-resistant alloy as the clad material are melted by a known method such as a converter, an electric furnace, or a vacuum melting furnace, and then a slab is made by a continuous casting method or an ingot casting-blotting method. The obtained slab is hot rolled under normally used conditions to obtain the clad material and the base material as hot-rolled sheets. The obtained hot-rolled sheet may be annealed, pickled, polished, etc., as necessary. The insert material is inserted between the above cladding material and the base material, and the cladding material is assembled by laminating the cladding material so that the bonding surface is vacuum, and the four circumferences of the bonding surface are sealed by welding. Examples of the method of inserting the insert material include a method of assembling the cladding material by sandwiching a foil, and a method of assembling the cladding material by using a base material or cladding material whose surface has been plated in advance. When assembling the cladding material by sandwiching a foil, the insert material is manufactured in the same manner as the above base material until hot rolling, and then cold rolling is performed to roll it to a predetermined thickness, and annealing and pickling are performed as necessary. The method of vacuuming the bonding surface is not particularly specified, but examples include a method of electron beam welding in a vacuum, a method of opening a hole for vacuuming in advance, welding four circumferences by arc welding or laser welding in the atmosphere, and then vacuuming with a vacuum pump. If the degree of vacuum is 0.1 Torr or less, a good bonding interface with less oxides at the interface can be obtained, and more preferably 0.05 Torr or less. Since the higher the degree of vacuum, the better the bonding interface tends to be, no lower limit is set. The obtained clad material may be subjected to hot rolling as it is as a clad rolling material, or two clad materials may be assembled by applying a release agent between them and stacking them, and then subjected to hot rolling as a clad rolling material. When stacking two materials, it is desirable that the base materials and clad materials are of equal thickness to reduce plate warping during cooling. Of course, the clad assembly method and the method of inserting the insert material do not have to be limited to those described above.
[0060] 6-2. Heating of rolling materials Next, the obtained clad rolled material is calculated by formula (2) using the maximum heating temperature Temp (℃) in the heating furnace and the time Time (min) from when the heating temperature in the heating furnace reaches the maximum heating temperature Temp-20℃ to when it is removed from the heating furnace. Heating is performed so that the calculated clad heating parameter value d (μm) is less than the thickness Thick (μm) of the inserted insert material. If d (μm) exceeds the thickness Thick (μm) of the inserted insert material, Cr diffuses to the base material side, so the width of the region where martensitic transformation can occur near the interface between the base material and the insert material becomes large, and the hydrogen embrittlement resistance of the interface decreases. Preferably, d is less than 0.7×Thick. d=2.27×10 5 ×√(Time)×exp(-1.64×10 4 / (Temp+273))...Equation (2)
[0061] The maximum heating temperature Temp (°C) in the heating furnace, the time Time (min) from when the heating temperature in the heating furnace reaches the maximum heating temperature Temp-20°C until the insert material is removed from the heating furnace, and the thickness Thick (μm) of the insert material may be appropriately determined so as to satisfy the above relationship, but preferred ranges are shown below in terms of properties other than the hydrogen embrittlement resistance of the interface and manufacturability. The maximum heating temperature Temp in the heating furnace is preferably 1050°C or more and 1250°C or less. If the maximum heating temperature Temp is less than 1050°C, the hot workability deteriorates and the joining strength also deteriorates. Therefore, the maximum heating temperature Temp is preferably 1050°C or more, and more preferably 1100°C or more. On the other hand, if the maximum heating temperature Temp exceeds 1250°C, the steel billet may deform in the heating furnace, defects may easily occur during hot rolling, the grain size of the base material may become large, the strength and toughness may decrease, and diffusion at the interface may become fast. Therefore, the maximum heating temperature Temp is preferably 1250°C or less, and more preferably less than 1200°C. The shorter the time (minutes) from when the heating temperature in the heating furnace reaches the maximum heating temperature Temp-20°C until the steel is removed from the heating furnace, the shorter the element diffusion distance at the interface will be, so no lower limit is set; however, heating for 30 minutes or more is desirable in order to uniformly distribute the temperature up to the center of the plate thickness. The thicker the insert material is, the more it suppresses Cr diffusion from the cladding material to the base material, but from the viewpoint of the cost of the insert material, it is desirable to keep it below 500 μm. Also, if the thickness is thin, restrictions will be imposed on the maximum heating temperature Temp and heating time Time, which will increase the manufacturing cost, so it is desirable to keep it above 30 μm. More desirable is a thickness of 50 μm or more and below 200 μm.
[0062] As mentioned above, the size of the martensite phase region at the interface is mainly affected by the diffusion of Cr. Although Cr diffusion occurs at temperatures of several hundred degrees Celsius or more, the diffusion distance increases exponentially as the temperature increases, so the actual diffusion occurs during the material heating period when it is held near the maximum temperature. In addition, the sheet temperature drops quickly during rolling and cooling, so the diffusion is negligibly small. Therefore, it is sufficient to consider the heating temperature and time for Cr diffusion.
[0063] 6-3.Hot rolling The heated rolled material is then hot rolled to the desired thickness. Hot rolling can be performed under appropriate rolling conditions according to the desired properties, such as the corrosion resistance of the clad material and the strength and toughness of the base material. If annealing is performed after rolling, the value calculated using formula (2) with the annealing temperature (℃) and annealing time (min) must be less than the value obtained by dividing the thickness of the insert material (Thickness: μm) by the reduction ratio. Here, the reduction ratio is calculated as the thickness of the clad material divided by the thickness of the product.
[0064] According to the present invention, it is possible to obtain a clad steel plate having excellent hydrogen embrittlement resistance at the joining surface. The clad steel plate according to the present invention and a welded structure made using the clad steel plate according to the present invention do not require measures against peeling during welding or additional heat treatment. Furthermore, the clad steel plate is not limited in its use and can be applied to structural members where solid steel plates have been used in the past. Therefore, the clad steel plate greatly contributes to cost reduction. The welded structure made using the clad steel plate according to the present invention can be a welded structure manufactured by a manufacturing process including welding or gouging using a gas containing hydrogen.
[0065] The clad steel plate of the present invention has excellent resistance to hydrogen embrittlement, and therefore, even when used in welding using hydrogen as the welding gas, hydrogen embrittlement does not occur under normally expected welding conditions. EXAMPLES
[0066] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0067] A clad material having the composition shown in Table 1 and a base material having the composition shown in Table 2 were melted and formed into billets, and the clad material was hot-rolled, annealed, pickled, or surface-polished to produce a 30 mm thick steel plate for the clad material and a 130 mm thick steel plate for the base material. A 50-200 μm thick foil having the composition shown in Table 3 was inserted between the obtained clad material and base material as an insert material, and the laminated materials were laminated so that the bonding surface was in a vacuum, and the four circumferences of the bonding surface were sealed by welding to produce a clad rolled material. The obtained clad rolled material was hot-rolled under the hot-rolling conditions shown in Table 4 to produce a clad steel plate having a thickness of 16 mm. In Tables 3 and 4, values and items outside the range of the present invention are underlined.
[0068] [Table 1]
[0069] [Table 2]
[0070] [Table 3]
[0071] The rolling conditions for clad steel plates were changed as shown in Table 4, and each characteristic value was investigated. The manufacturing conditions in Table 4 are explained below. In Table 4, Temp indicates the maximum heating temperature (°C) in the heating furnace before rolling, and Time indicates the time (minutes) from when the heating temperature in the heating furnace reached the maximum heating temperature Temp-20°C to when it was removed from the furnace. Thick indicates the thickness (μm) of the insert material inserted during assembly. d indicates the value (μm) of the clad heating parameter calculated from the above Temp and Time using formula (2). d=2.27×10 5 ×√(Time)×exp(-1.64×10 4 / (Temp+273))...Equation (2)
[0072] In Table 4, L indicates the width (μm) of the region near the interface where the nanohardness is 7 GPa or more. Nanohardness measurements were performed in accordance with the instrumented indentation hardness test specified in ISO 14577, with measurements being performed on the base material side and the insert material side, over a range of 10 μm from the interface in the plate thickness direction, at 0.5 μm intervals. The conditions for nanohardness measurement can be selected as appropriate, but an example would be a measurement where a load of 1000 μN is used, indentation is performed for 5 seconds up to the specified load, held for 0 seconds, and returned for 5 seconds, three times at each position, and the average value is taken as the nanohardness. The range of the region where the nanohardness is 7 GPa or more was read and taken as L.
[0073] The following tests were carried out to evaluate hydrogen embrittlement resistance. To ensure the length in the plate thickness direction, the test specimens were prepared by welding the same steel type as the clad material to the clad material side of the clad steel plate, and the same steel type as the base material to the base material side, with the parallel part including the clad interface being 4φ×20mm, and a 60°, ρ=0.1mm notch was added to the clad interface to give a 3φ round bar test specimen. To suppress the thermal effects of welding, electron beam welding was selected as the welding method, which has a small heat input and can reduce the width of the weld metal, and grinding was carried out after welding. The cross-section of the test specimen was also observed to confirm that the weld metal was at least 2mm away from the interface. Before tension, the prepared test specimen was immersed in a 3 mass% NaCl + 3 g / L NHSCN aqueous solution at a current density of 10 (A / m 2 ) × 72(hr), then in a 3%NaCl+3g / L NHSCN aqueous solution at 10(A / m 2 ) Strain rate of parallel section while cathodically charging: 1×10 -3 A separate test was conducted in which the specimen was pulled without cathodic charging before and during the pulling process, and the strokes to break were compared. If the stroke of the charged specimen / the stroke of the uncharged specimen was 0.25 or more, it was evaluated as good (○), and if it was less than 0.25, it was evaluated as poor (×). This is shown in the "Hydrogen resistance" column in Table 4.
[0074] To evaluate toughness, three 10 mm thick, 2 mm V-notch test pieces conforming to JIS Z 2241 were taken from a depth of 1 mm to 11 mm from the surface layer on the base metal side, and a Charpy impact test was carried out at a test temperature of -40°C. The lowest of the three impact values obtained is shown in the "Impact Value" column in Table 4. The impact value was 50 J / cm 2 If the intensity is more than 100 J / cm, there is no problem in practical use. 2 That's all.
[0075] The manufacturing conditions and the above results are summarized in Table 4 and Figure 1. Figure 1 shows the difference (Thick-d) between the value of the cladding heating parameter calculated from formula (2) and the thickness Thick of the inserted insert material on the horizontal axis, and the width L of the region at the interface where the nanohardness is 7 GPa or more on the vertical axis, with ○ indicating good hydrogen embrittlement resistance and × indicating poor hydrogen embrittlement resistance. The plots marked "insert material unsuitable" in the figure indicate that the component composition of the insert material is outside the suitable range. When Thick-d<0 or when the insert material is unsuitable, L exceeds 5 μm and hydrogen embrittlement resistance is poor.
[0076] [Table 4]
[0077] Numbers 1 to 41 in Table 4 are examples of the present invention that satisfy the preferred manufacturing conditions, have a length L of 5 μm or less where the nanohardness is 7 GPa or more, and have good hydrogen embrittlement resistance of the bonded surfaces. Numbers 42 to 47 are comparative examples that do not satisfy the preferred manufacturing conditions, have a length L of 5 μm or more where the nanohardness is 7 GPa or more, and have poor hydrogen embrittlement resistance of the bonded surfaces.
[0078] As described above, the examples of the present invention provided good resistance to hydrogen embrittlement of the bonded surfaces, whereas the comparative examples did not satisfy the preferred manufacturing conditions and the length L of the region with a nano-hardness of 7 GPa or more was outside the range specified by the present invention, resulting in poor resistance to hydrogen embrittlement of the bonded surfaces. [Industrial Applicability]
[0079] According to the present invention, a clad steel plate having good hydrogen embrittlement resistance at the bonding surface can be obtained, which is extremely useful in industry. If a corrosion-resistant alloy is used as the clad material, the clad steel plate of the present invention may be applicable to corrosive environments such as high chloride environments exposed to seawater, and corrosive environments in plant facilities exposed to acid solutions such as phosphoric acid or sulfuric acid. Specific examples include seawater desalination plants, flue gas desulfurization equipment, storage tanks for chemicals, structural members such as oil well tubular goods, pumps and valves, and heat exchangers. [Explanation of symbols]
[0080] L: Width of the region at the interface where the nanohardness is 7 GPa or more (μm) Thickness: Thickness of the insert material in rolled material (μm) d: Value of the cladding heating parameter calculated by equation (2) (μm)
Claims
1. A clad steel plate comprising a base material and a clad material joined to the base material, The base material is made of carbon steel or low alloy steel, The cladding material is made of a corrosion-resistant alloy, The structure has an insert material inserted between the base material and the cladding material, The base material has a composition, in mass%, of C: 0.020 to 0.200%, Si: 1.00% or less, Mn: 0.10 to 3.00%, P: 0.050% or less, S: 0.050% or less, Ceq is 0.20 to 0.40, and the balance is Fe and impurities; The insert material is a steel or a Ni-based alloy containing, by mass%, Ni: 20% or more and Cr: less than 10%, or pure Ni; A clad steel plate, characterized in that at the interface between the base material and the insert material of the clad steel plate, the width in the plate thickness direction of a region having a nano-hardness of 7 GPa or more is 5 μm or less. Here, Ceq is defined by the following equation (1). Ceq=C+Mn / 6+(Cu+Ni) / 15+(Cr+Mo+V) / 5...Equation (1)In the equation, C, Mn, Cu, Ni, Cr, Mo and V are the contents (mass%) of each element in the composition of the base steel plate. For elements that are not contained, the content of the element is set to 0 and the calculation of formula (1) is performed.
2. The composition of the base material further contains, in mass%, one or more selected from Ni: 0.01 to 1.00%, Cr: 0.01 to 1.00%, Mo: 0.01 to 0.50%, Cu: 0.01 to 1.00%, Co: 0.01 to 0.50%, Se + Te: 0.01 to 0.10%, V: 0.001 to 0.100%, Ti: 0.001 to 0.200%, Nb: 0.001 to 0.200%, Al: 0.005 to 0.300%, Ca: 0.0003 to 0.0050%, B: 0.0003 to 0.0030% and REM: 0.0003 to 0.0100%, in place of a portion of the Fe. Clad steel plate according to claim 1.
3. 3. The clad steel plate according to claim 1, wherein a clad material of the clad steel plate is a stainless steel or a nickel-based alloy containing, by mass%, 10% or more of Cr.
4. A method for manufacturing a clad steel plate according to any one of claims 1 to 3, comprising inserting an insert material between a base material and a cladding material, laminating the cladding material so that the bonding surface is in a vacuum, and sealing four peripheries of the bonding surface by welding to form a clad material, and using the cladding material as it is as a clad rolling material, or assembling two or more of the cladding materials to form a clad rolling material, and determining a maximum heating temperature Temp (°C) in a heating furnace for the clad rolling material, and determining whether the heating temperature in the heating furnace is a maximum heating temperature Temp (°C) in the heating furnace. A method for manufacturing a clad steel plate, characterized in that after heating, the value of the clad heating parameter d (μm), calculated from equation (2) using the time Time (minutes) from when the temperature Temp reaches -20°C to when the plate is removed from the heating furnace, is less than the thickness Thick (μm) of the inserted insert material, and hot rolling is performed, so that the width in the plate thickness direction of the region at the interface between the base material and the insert material where the nano-hardness is 7 GPa or more is 5 μm or less. d = 2.27 × 10 5 ×√(Time)×exp(-1.64×10 4 / (Temp+273))…Formula (2)
5. A welded structure made using the clad steel plate according to any one of claims 1 to 3.
6. The clad steel plate according to any one of claims 1 to 3, characterized in that the clad steel plate is used for welding using hydrogen as a welding gas.
Citation Information
Patent Citations
Method for stabilizing aluminum lactate
JP1986027939A
Production of two-phase stainless steel clad steel
JP1987110880A
Production of high alloy clad steel plate having excellent corrosion resistance
JP1987137108A
Production of clad steel stock of austenitic stainless steel
JP1994007803A
HIGH TOUGHNESS HIGH CORROSION RESISTANCE Ni ALLOY CLAD STEEL SHEET EXCELLENT IN WELD ZONE TOUGHNESS AND PRODUCTION METHOD THEREOF
JP2014101568A